How Can Journalists Strengthen Their Fight Against Misinformation in a Changing Media Landscape? - Marina Tulin; Michael Hameleers; Christofer Talvitie; Claes de Vreese (VIEW Journal of European Television History and Culture)
This paper reflects on challenges and opportunities for journalistic practices in the fight against misinformation in light of recent changes in the online media landscape. On the one hand, recent innovations in technology and social media facilitate a rapid spread of disinformation placing increased pressure on journalists to fight falsehoods and (re)build trust in reliable information. On the other hand, journalists might be positively affected by the EU’s recent introduction of the Digital Services Act (DSA), which aims to regulate online platforms and facilitate the fight against mis- and disinformation.